2022
DOI: 10.1371/journal.pone.0273504
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptide DGL13K is active against drug-resistant gram-negative bacteria and sub-inhibitory concentrations stimulate bacterial growth without causing resistance

Abstract: Antimicrobial peptides may be alternatives to traditional antibiotics with reduced bacterial resistance. The antimicrobial peptide GL13K was derived from the salivary protein BPIFA2. This study determined the relative activity of the L-and D-enantiomers of GL13K to wild-type and drug-resistant strains of three gram-negative species and against Pseudomonas aeruginosa biofilms. DGL13K displayed in vitro activity against extended-spectrum beta-lactamase (ESBL)-producing and Klebsiella pneumoniae carbapenemase (KP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The Gram-negative bacteria P. aeruginosa are highly susceptible to both LGL13K and DGL13K, showing only a 2-4-fold difference in MIC between the two peptide isomers (24, 27, 28). In fact, in a serial peptide exposure experiment, the MIC only increased about 2-fold for LGL13K and this increase was not statistically significant, suggesting that the bacteria are not able to mount resistance to either peptide stereoisomer (27). To validate this finding, P. aeruginosa was serially exposed to LGL13K or DGL13K.…”
Section: Resultsmentioning
confidence: 99%
“…The Gram-negative bacteria P. aeruginosa are highly susceptible to both LGL13K and DGL13K, showing only a 2-4-fold difference in MIC between the two peptide isomers (24, 27, 28). In fact, in a serial peptide exposure experiment, the MIC only increased about 2-fold for LGL13K and this increase was not statistically significant, suggesting that the bacteria are not able to mount resistance to either peptide stereoisomer (27). To validate this finding, P. aeruginosa was serially exposed to LGL13K or DGL13K.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that three strains of P. gingivalis (W50, ATCC 53977 and DPG3) are resistant to LGL13K but not to the endogenous antimicrobial peptide LL-37 (43). We have since designed an all-D amino acid version of this peptide (DGL13K) (53), which resists proteolytic degradation and kills both Gram negative and Gram positive bacteria (53)(54)(55)(56). Timed-kill assays showed that P. gingivalis W50 were killed by DGL13K but not LGL13K or polymyxin B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from immunomodulators, AMPs, a class of peptides with diverse sequences and structures, offer several key advantages over antibiotics due to high potency, ability to tackle a broad spectrum of microbes, multiple modes of action and low risk of AMR development. [50][51][52][53] These peptides, particularly the ones with cationic or anionic charges, can disturb the membrane of bacteria, interrupt the enzyme activity, or interact with their intracellular components, causing apoptosis or necrosis through various models, depending on the bacterial strains. 54 Nonetheless, AMPs as therapeutic agents may be restricted due to their instability in physiological salt concentrations, susceptibility to protease degradation, hemolytic activity, inconsistency in their impacts on bacterial membranes and toxicity to mammalian cells.…”
Section: Current Strategies For Controlling Infections and Detecting ...mentioning
confidence: 99%